THE ROLE OF ISLAMIC SOCIAL MARKETING AS A MEDIATION VARIABLE ON THE IMPLEMENTATION OF MAQASHID SYARIAH ON DECISIONS TO PAY ZIS THROUGH ZAKAT MANAGERS - NURIDA ISNAENI; MUHAMMAD QODRI (Al-Masraf: Jurnal Lembaga Keuangan dan Perbankan, 2019)
This study aimed to analyze the effect of application of Maqashid Syariah on the decision of Muzaki in paying ZIS, to analyze the effect of the application of Maqashid Syariah on social marketing carried out by zakat managers, and to analyze the effect of social marketing on Muzaki decision in paying ZIS. Finally, to analyze whether social marketing is able to mediate between maqashid syariah towards Muzaki decision in paying ZIS to zakat managers. This study used the Structural Equation Model (SEM) method with quantitative descriptive analysis by using software tools, Lisrel and SPSS. in this study used a sample of 360 respondents who became muzaki (zakat payers) in Jambi province. The results of the SEM method concluded that the Maqashid Syariah variable directly affected social marketing, while not directly towards the decision to pay ZIS. Direct social marketing also influences the decision to pay ZIS. Finally, in this study, social marketing as an intervening variable provided mediation effect (direct mediation) indirect only between maqashid syariah and the decision to pay ZIS.